User authentication scheme based on the ElGamal signature for mobile communication system - LI Wei-ke; LI Fang-wei (Tongxin xuebao)
An efficient user authentication protocol was presented for a digital mobile communication system based on the EIGamal signature. Compared with the original scheme, the new scheme had improved the security performance of the network center as well as reduced the cost calculation of the user through improvements made in the authentication process. The analysis of the new scheme shows that the modified scheme is of higher security and lower calculative complexity, which satisfies the requirements of mobile communication.